2000
DOI: 10.1385/endo:13:3:281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Dietary Exposure to Genistein, a Phytoestrogen, During Various Stages of Development on Reproductive Hormones and Spermatogenesis in Rats

Abstract: Developmental, hormonal, and gametogenic parameters were evaluated in male progeny following chronic dietary exposure to the phytoestrogen genistein. Twenty pregnant rats were fed a diet containing genistein (50 microg/d) from d 17 of gestation, and 12 were fed a control diet without genistein. Four litters each of control and genistein-fed rats were euthanized on d 21. The remaining pups were weaned on d 21 and only male rats were used in this study. On d 21, eight litters of genistein-fed rats were placed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 35 publications
6
38
2
1
Order By: Relevance
“…More so, report by Bahmanpour et al (2006) confirmed that Phoenix dactylifera have gonadotrophin-like effects which could be due to its steroidal components. The date phytochemicals genistein (Roberts, Veeramachaneni, Schlaff, & Awoniyi, 2000;Eustache et al, 2009), vitamin A (Bartlett, Weinbauer, & Nieschlag, 1989) and selenium (Jana et al, 2008) have all been reported to protect testicular functions against various stress and possess gonadotropic activity, and the presence of these compounds may have contributed to the observed ameliorating effects recorded here in.…”
Section: Resultsmentioning
confidence: 66%
“…More so, report by Bahmanpour et al (2006) confirmed that Phoenix dactylifera have gonadotrophin-like effects which could be due to its steroidal components. The date phytochemicals genistein (Roberts, Veeramachaneni, Schlaff, & Awoniyi, 2000;Eustache et al, 2009), vitamin A (Bartlett, Weinbauer, & Nieschlag, 1989) and selenium (Jana et al, 2008) have all been reported to protect testicular functions against various stress and possess gonadotropic activity, and the presence of these compounds may have contributed to the observed ameliorating effects recorded here in.…”
Section: Resultsmentioning
confidence: 66%
“…Simultaneously, some authors reported that there are no significant effects of phytoestrogens in rodents (Roberts et al, 2000;Mitchell et al, 2001;Lamartiniere et al, 2002). One of the explanations for these inconsistent results is that commercial rodent diets all contain high and variable levels of abundant phytoestrogens, which could affect results of studies on reproductive toxicity of test phytoestrogens (Odum et al, 2001;Stroheker et al, 2003;Naciff et al, 2004;Thigpen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have examined the effects of single EDC using in vitro or in vivo assays (Christiansen et al, 2010;Roberts et al, 2000), few studies have been conducted to examine the eff ects of mixtures of EDCs on mammalian reproductive development, especially for those EDCs that act via diff erent mechanisms. So as a result of growing concerns about mixture exposure in reality recently, research on EDC mixture exposure during pregnancy and lactation have became a focus in andrology and toxicology (Kortenkamp, 2008).…”
Section: Introductionmentioning
confidence: 99%